Upaya meningkatkan prestasi belajar PPKN melalui model pembelajaran kooperatif tipe students team achievement division (STAD) - I Made Wirta (Indonesian Journal of Educational Development, 2021)
This classroom action research aims to improve student achievement by applying the Students Achievement Division (STAD) type of cooperative learning model. The subjects of this study were 36 students of class XI MIPA6 SMA Negeri 1 Sukawati in the odd semester of the 2019/2020 academic year. While the object of research is the learning achievement of PPKn. The data collection methods used were observation and learning achievement tests, which were then analyzed using descriptive methods for both qualitative and quantitative data. The criteria for the success of action research are determined based on the average value of learning achievement classically at least equivalent to the KKM score of 75. The results showed the learning process by applying the STAD type cooperative learning model can improve student achievement. This is evident from the completeness of student learning in Cycle I amounted to 86.11% and an average of 73.61 increased in Cycle II completeness of 94.44% and an average of 78.47%. The conclusion from this research is that the type of STAD cooperative learning model can improve student achievement. Penelitian tindakan kelas ini bertujuan untuk meningkatkan prestasi belajar siswa dengan penerapan model pembelajaran kooperatif tipe Students Achievement Division (STAD). Subjek penelitian ini adalah siswa kelas XI MIPA6 SMA Negeri 1 Sukawati semester ganjil tahun pelajaran 2019/2020 yang berjumlah 36 orang. Sedangkan objek penelitian adalah prestasi belajar PPKn. Metode pengumpulan data yang digunakan adalah observasi dan tes prestasi belajar yang selanjutnya dianalisis dengan metode deskriptif baik untuk data kualitatif maupun untuk data kuantitatif. Kriteria keberhasilan penelitian tindakan ditetapkan berdasarkan nilai rata-rata prestasi belajar secara klasikal minimal setara dengan nilai KKM sebesar 75. Hasil penelitian menunjukan proses pembelajaran dengan penerapan model pembelajaran kooperatif tipe STAD dapat meningkatkan prestasi belajar siswa. Ini terbukti dari ketuntasan belajar siswa pada Siklus I sebesar 86,11% dan rata rata 73,61 meningkat pada Siklus II ketuntasan sebesar 94,44% dan rata rata 78,47%. Kesimpulan yang diperoleh dari penelitian ini adalah model pembelajaran kooperatif tipe STAD dapat meningkatkan prestasi belajar siswa.